Evaluation of aerobic capacity in cross country skiers - Balestreri, F.; Schena, F. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Cross country skiing is well know as a typical aerobic sport. For this reason it has been of great interest for exercise physiologists and it is regarded as one of the most demanding endurance sport. The evaluation of the athletes involved in this sport were usually performed by treadmill testing during upgrade running or walking with poles. In the last two decades the deep performance changes, related to the introduction of skating technique and progress in materials and track management, have also modified the evaluation requirements in order to improve the knowledge of physiological determinants and to offer more appropriate information for training. The role of upper body in the propulsive force generation emerged to be more and more important and this aspect became a central argument in research and elaboration of new evaluation protocols ( Wisloff & Helgerud, 1998). Several studies stated that upper body sustainable workload and the related aerobic capacity is closed related to skiing performance. By physiological point of view the special interest is that the athletes have an extraordinary high aerobic capacity and that both upper and lower body muscles are involved to various degrees with different techniques (Van Hall et al. 2003). Recently it has been shown that ski-specific laboratory testing, such as treadmill roller skiing or upper body ergometer, is better able to predict skiing performance when compared to treadmill running or walking with poles ( Mahood, 2001). On the other hand there are growing possibilities to execute evaluation and testing also on snow track, in very controlled conditions, even if this appears to be more appropriate for physiological studies (Formenti et al., 2005) than for prediction of performance at elite level due the deficit in extreme slope track. In the last three years our laboratory, with the co-operation of the Technical Staff of FISI and the Institute of Sport Science from CONI, developed and compared several protocols to determine aerobic capacity in cross country elite skiers, also with field testing and motion analysis. The actual procedure, including the measurement of the force applied on the poles during diagonal technique on treadmill, was successfully applied to the national teams in the last training season and the preliminary results will be described in this presentation.